Trials of clear aceclofenac-loaded soft capsules with accelerated oral absorption in human subjects - Yong, Chul Soon; Oh, Yu-Kyoung; Lee, Kyung Hee; Park, Sang-Man; Park, Young-Joon; Gil, Young Sig; Yu, Chang Hun; Yoo, Bong-Kyu; Woo, Jong Soo; Kim, Jong Oh; Rhee, Jong-Dal; Kim, Chong-Kook; et al. (International journal of pharmaceutics, 2005)
To develop an effective oral drug delivery system with accelerated absorption in human subjects for a poorly water-soluble acelofenac, five aceclofenac-loaded soft capsule preparations containing various ratios of different solubilizers were prepared and their dissolution tests were carried out. Among five preparations tested, a preparation with ethanolamine was selected as a formula of aceclofenac soft capsule (Korea United Pharm. Co. Ltd., Clanza S™), since it was clear in appearance and showed the fastest dissolution rate due to the solubility-enhancing effect of aceclofenac. To evaluate and compare the pharmacokinetics of acelofenac-loaded soft capsules with the conventional aceclofenac tablets (Dae-Woong Pharm. Co. Ltd., Airtal™) in human subjects; 14 normal healthy male volunteers (age 20–25 years old) were divided into two groups and a randomized 2 × 2 cross-over study was performed. Following oral administration of one tablet or capsule, each containing 100 mg of aceclofenac, blood samples were collected at the predetermined time intervals and the concentration of aceclofenac in plasma was determined by HPLC method using UV detector. The AUC, C max, MRT, t 1/2 and K el of aceclofenac delivered from soft capsule were not significantly different from those from aceclofenac-loaded conventional tablet. However, soft capsule gave significantly higher initial concentration and significantly faster T max of aceclofenac than did conventional tablet, suggesting that the soft capsule with ethanolamine showed the faster absorption of aceclofenac in human subjects. Thus, the clear aceclofenac-loaded soft capsule with ethanolamine was a more effective oral dosage form with fast absorption for poorly water-soluble aceclofenac.